AB0206 Investigation of the inducibility of retroviruses from rheumatoid arthritis synovial fibroblasts (ra-sf) and ra-synovial fluid cells (ra-sfc). (1st June 2001) - Seemayer, CA; Kolb, SA; Böni, J; Neidhart, M; Simmen, B; Gay, RE; Michel, BA; Schüpbach, J; Gay, S
Abstract : Background: Objectives: In many investigations virus like particles (VLP) and especially type-C retroviruses could be activated from tumour cells in culture after stimulation with DNA damaging agents. Co-culture with H9 cells, a lymphatic cell line, has been successfully used to isolate exogenous human retroviruses such as HTLV and HRV-5. The aim of this study was to induce potentially hidden retroviruses from cell cultures from RA patients and to analyse for VLP and reverse transcriptase (RT)-activity. Methods: Rheumatoid arthritis synovial fibroblasts (RA-SF) were derived from synovial biopsies and synovial fluid cells from RA synovial fluids. Normal skin fibroblasts served as controls for the RA-SF and SFC from arthritis urica as well as unclassified oligoarthritis for the RA-SFC. As positive control we used baby hamster kidney cells, murine mast cells and pig fibroblasts, which produce endogenous retroviruses. Subconfluent RA-SF and controls were incubated with azacytidin (AzaC: 2 μg/ml for 24 h), bromodeoxyuridine (BUDR: 25 μg/ml for 24 h) or irradiated with 2 or 8 Gy X-rays, respectively. Supernatants of cell cultures were taken after 24 h or 48 h and analysed for RT-activity by the product enhanced reverse transcriptase (PERT)-assay. The cells were harvested on days 2–6 without trypsinization, fixed in glutaraldehyde and prepared for electron microscopy. Furthermore, RA-SF and RA-SFC were co-cultured with H9 cells for more than 3 weeks, and the supernatant was collected every 3–4 days and analysed by the PERT-assay. Results: In the virus induction and co-culture experiments, no evidence for RT-activity could be detected. In contrast, the positive controls including supernatants of cell cultures from baby hamster kidney cells, murine mast cells and pig fibroblasts revealed a strong positive RT-activity. The electron microscopical investigation of the AzaC, BUDR treated or irradiated cells did not reveal VLP. Conclusion: The current investigation does not support the involvement of infectious retroviruses in RA, but cannot exclude a role of exogenous and/or endogenous retroviruses, or the involvement of endogenous retroviral elements in the pathogenesis of RA. C. A. Seemayer supported by the DAAD and by the Theodor und Ida Herzog-Egli Stiftung, all others by their institutions.